Analisa Perencanaan Strategis Sistem Informasi di Departemen Manajemen Aset Bina Nusantara - Arifin, Firman (Bina Nusantara University, 2010)
The objective of this paper is to analyse portofolio application and information technology that is used today in Asset Management Department of Bina Nusantara so it could be made a strategic planning information system that could accommodate business needs. The discussion is focused to a strategic analysis that is applied today and its improvement in the future including information technology structure. The conclusion from this paper is along with a good information technology strategic planning, expected work effectivity and efficiency could be reached.